Investigation of the relationship between miR-33a, miR-122, erythrocyte membrane fatty acids profile, and serum lipids with components of metabolic syndrome in type 2 diabetic patients - Fatemeh Masoudi; Mohammad Reza Sharifi; Morteza Pourfarzam (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: MicroRNAs (miRNAs) are small non-coding RNA molecules acting as critical regulators of post-transcriptional gene expression. MiR-33a and miR-122 have a crucial role in cholesterol and lipid metabolism. Therefore, their dysregulation may contribute to metabolic abnormality and their inhibition may be a useful therapeutic strategy. The objective of the present study was to investigate the relationship between miR-33a, miR-122, erythrocyte membrane fatty acids profile, and serum lipids with components of metabolic syndrome in an Iranian population suffering from type 2 diabetes mellitus (T2DM). Experimental approach: Expression of miR-33a and miR-122 was measured by real-time polymerase chain reaction and erythrocyte membrane fatty acid profiles were analyzed by gas chromatography-mass spectrometry. Findings/Results: T2DM patients with and without metabolic syndrome had significantly higher miR-33a and miR-122 levels compared to controls. MiRNAs were significantly correlated with saturated fatty acid (SFAs), total SFAs/total polyunsaturated fatty acids (PUFAs) ratio, fasting plasma glucose, triacylglycerols, insulin and homeostatic model assessment of insulin resistance. In addition, there was a significant negative correlation between miR-33a and miR-122 levels and PUFAs, total PUFAs/total SFAs ratio and omega 6 fatty acids. Conclusion and implications: Considering the roles of miR-33a and miR-122 in cholesterol and lipids metabolism, it may be concluded that the measurement of their expression may be useful as a potential additional biomarker for cardiometabolic derangement in T2DM patients. In addition, these findings may suggest that the inhibition of these miRNAs by anti-miRNA therapies may be explored as a potential therapeutic strategy.